2022
DOI: 10.3390/ijerph19159070
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Causality between Spreading COVID-19 and Individual Mobilisation with Consumption Motives across Prefectural Borders in Japan

Abstract: A combination of pharmaceutical and non-pharmaceutical interventions as well as social restrictions has been recommended to prevent the spread of coronavirus disease 2019 (COVID-19). Therefore, social contact surveys play an essential role as the basis for more effective measures. This study attempts to explore the fundamental basis of the expansion of COVID-19. Temporal bidirectional causalities between the numbers of newly confirmed COVID-19 cases (NCCC) and individual mobilisations with consumption motives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Alcohol consumption tended to elicit behavior that promotes lower compliance to COVID-19 preventive measures ( 74 ). Indeed, individual mobilizations with expenditures to pubs across the prefectural borders played important roles in expanding the COVID-19 pandemic in Japan ( 76 ). Furthermore, a recent scoping review study revealed that rural were associated with an increased likelihood of hazardous alcohol use or alcohol-related harm compared to urban ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol consumption tended to elicit behavior that promotes lower compliance to COVID-19 preventive measures ( 74 ). Indeed, individual mobilizations with expenditures to pubs across the prefectural borders played important roles in expanding the COVID-19 pandemic in Japan ( 76 ). Furthermore, a recent scoping review study revealed that rural were associated with an increased likelihood of hazardous alcohol use or alcohol-related harm compared to urban ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…25 , 26 SSNPA provides annual suicide numbers in Japan disaggregated by various factors, including sex (male and female), school (middle school, high school, and university), and suicidal motives (7 categories: family, health, economic, employment, romance, school related, and other motives, with 52 subcategories) (eTables 1, 2, and 3 in Supplement 1 ). 8 , 16 , 18 , 25 , 26 , 27 , 28 , 29 The detailed methods of the investigation of suicidal motives are explained in the eAppendix in Supplement 1 . Annual student populations in middle school, high school, and university from 2007 to 2022 (denominator for SMRP derivation) were obtained from the School Basic Survey, a government database of the Ministry of Education, Culture, Sports, Science and Technology.…”
Section: Methodsmentioning
confidence: 99%
“…However, CSMRs disaggregated by age in Japan have increased in an age‐dependent manner in the <60 years population. 7 , 8 , 12 , 28 , 34 , 35 Therefore, when suicide risk is age‐dependent and the age distribution in regions changes over time, age distribution becomes an important demographic variable for suicide statistics. In Japan, which has a decreasing birth rate and aging population (predominant in rural areas), even if CSMRs for each generation remain stable, national‐level CSMRs may increase due to aging.…”
Section: Basis Of Statistical Measures For Suicide Mortality Trendsmentioning
confidence: 99%
“… 65 VAR is usually summarized by structural analyses using Granger causality, 66 impulse responses, and forecast error variance decompositions. 12 , 13 , 14 , 35 Granger causality is statistical hypothesis test for determining whether time‐series analysis is effective in forecasting the result. 66 The impulse response explains the evolution of the model's variables in reaction to a shock in one or more variables.…”
Section: Causality Analysesmentioning
confidence: 99%